Isolation and Mapping of Polynucleotide Phosphorylase Mutants of Escherichia coli - Reiner, Albey M. (1969)
Three strains of Escherichia coli with altered polynucleotide phosphorylase, Q7, Q13, and Q27, were isolated by screening clones from heavily mutagenized cultures for low levels of the enzyme. The three mutations were found to cotransduce with argG and asp, and the pnp locus which they define was mapped with respect to these loci. An explanation for the nonreciprocal cotransduction frequencies observed with asp is provided by the demonstration of an unlinked asp-suppressing locus.